Sub-cellular Electrical Heterogeneity Revealed by Loose Patch Recording Reflects Differential Localization of Sarcolemmal Ion Channels in Intact Rat Hearts - Kubasov, Igor V.; Stepanov, Andrei; Bobkov, Danila; Radwanski, Przemysław B.; Terpilowski, Maxim A.; Dobretsov, Maxim; Gyorke, Sandor (Frontiers in Physiology, 2018)
The cardiac action potential (AP) is commonly recoded as an integral signal from isolated myocytes or ensembles of myocytes (with intracellular microelectrodes and extracellular macroelectrodes, respectively). These signals, however, do not provide a direct measure of activity of ion channels and transporters located in two major compartments of a cardiac myocyte: surface sarcolemma and the T-tubule system, which differentially contribute to impulse propagation and excitation-contraction (EC) coupling. In the present study we investigated electrical properties of myocytes within perfused intact rat heart employing loose patch recording with narrow-tip (2 µm diameter) extracellular electrodes. Using this approach, we demonstrated two distinct types of electric signals with distinct waveforms (single peak and multi-peak AP; AP1 and AP2, respectively) during intrinsic pacemaker activity. These two types of waveforms depend on the position of the electrode tip on the myocyte surface. Such heterogeneity of electrical signals was lost when electrodes of larger pipette diameter were used (5 or 10 µm), which indicates that the electric signal was assessed from a region of < 5 µm. Importantly, both pharmacological and mathematical simulation based on transverse (T)-tubular distribution suggested that while the AP1 and the initial peak of AP2 are predominantly attributable to the fast, inward Na+ current in myocyte’s surface sarcolemma, the late components of AP2 are likely representative of currents associated with L-type Ca2+ channel and Na+/Ca2+ exchanger (NCX) currents which are predominantly located in T-tubules. Thus, loose patch recording with narrow-tip pipette provides a valuable tool for studying cardiac electric activity on the subcellular level in the intact heart.